Retrospective study of the incidence of sarcoidosis-like reaction in patients treated with immunotherapy. Issue 2 (February 2023) - Li, Y.; Flavell, R.R.; Juarez, R.; Chow, M.; Wu, C.; Tsai, K.; Daud, A.; Behr, S.C.
Abstract : Aim: To assess the frequency of radiographically evident drug-induced sarcoidosis-like reaction (DISR) in patients treated with anti-cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) therapy, anti-programmed cell death protein 1 (PD-1) therapy, or a combination of both in a single centre. Materials and methods: The images and medical records of 457 patients with metastatic melanoma or head and neck cancer treated with either anti-CTLA-4 therapy, anti-PD-1 therapy, or a combination of both at University of California medical centre were reviewed retrospectively and the incidence of radiological manifestations of DISR was assessed among these treatment groups. Results: Radiological manifestations of DISR were found in 19/457 patients (4.1%). The mean interval from the initiation of immunotherapy to development of DISR was 5.5 months (range 2.3–13.5 months). Mean interval from radiological detection of DISR to imaging evidence of resolution was 5.8 months (range 1.6–18.3 months). Three patients out of 81 (3.7%), 11/297 (3.7%), and 5/79 (6.3%) developed sarcoidosis-like reaction after treatment with anti-CTLA-4 antibody, anti-PD-1 antibody, and a combination of both, respectively. Most patients with DISR were asymptomatic and did not require systemic therapy. Most patients did not demonstrate concomitant increased maximum standardised uptake value (SUVmax) in other organs on their integrated 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) positron-emission tomography (PET)/computed tomography (CT). Conclusions: In the present retrospective study of patients treated with immune checkpoint inhibitors (ICIs), DISR occurred in approximately 3.7% of patients treated with either anti-CTLA-4 or anti-PD-1 antibody and 6.3% of patients treated with a combination of both. Highlights: Immune checkpoint inhibitors are associated with immune-related adverse events. Some adverse events can be detected on imaging and mistaken for metastatic lesions. Drug indued sarcoidosis-like reaction can manifest as lymphadenopathy. Individuals should be aware of this reaction as it can mimic disease progression.